1999
DOI: 10.1177/026921639901300517
|View full text |Cite
|
Sign up to set email alerts
|

Use of unlicensed medication in palliative medicine

Abstract: We were interested to read the paper by Atkinson and Kirkham 1 on the use of unlicensed medication in their palliative care unit, as we have just completed a similar study on the inpatient palliative care unit at the Royal Marsden Hospital, Sutton. The methodology of our study was very similar to that employed in the paper. However, we classified our drugs as either having a product licence for the specific indication (PLI), having a product licence for an alternative indication (PLNI), having a clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…A significant rate of off-label prescribing due to unapproved route of administration (11%) has also been identified [20]. These rates are slightly higher than we identified, but this is not unexpected.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A significant rate of off-label prescribing due to unapproved route of administration (11%) has also been identified [20]. These rates are slightly higher than we identified, but this is not unexpected.…”
Section: Discussionsupporting
confidence: 58%
“…In the specialist palliative care setting the rate of offlabel prescribing due to unlicensed indication has been found to be approximately 15% [1,20]. A significant rate of off-label prescribing due to unapproved route of administration (11%) has also been identified [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 But the fact that patients can still obtain care from hospitals and other community services, and alongside hospice and palliative care, means that the more intensive therapies, such as chemotherapy, radiotherapy, transfusion and more expensive treatments such as bisphosphonates for bone pain and hypercalcaemia, to improve symptoms or enhance life, can be given alongside other treatments. [46][47][48] There is also a growing emphasis on providing rehabilitation in hospices and palliative care services. 49 However, in the U.K. the primary focus of much palliative care is cancer.…”
Section: Higginson S-166mentioning
confidence: 99%
“…1 The practice is widespread, particularly in specialties such as paediatrics, pain medicine and palliative care, with up to one quarter of all prescriptions in the latter falling into this category. 2,3 Although such use of drugs is legal, there are implications for prescribers, as outlined in guidelines for best practice produced by regulatory bodies such as the General Medical Council (GMC). However, in a survey undertaken in 1999, we found that <5% of doctors in palliative care would always obtain verbal consent, document in the notes or inform other professionals of such use, as was then recommended by the GMC.…”
Section: Introductionmentioning
confidence: 99%